(untitled) - Investment U. (Hoboken, N.J., 2007)
At a time when commodities have taken a hefty hit—crude oil has dropped 28.8% from its high on May 2, gold is down more than 25%, and natural gas has corrected 49.5%—one commodity is moving higher by the day. The fact is, this wonder metal—uranium—is not only moving up, it's continued to set record highs throughout 2006, even during the most severe market corrections. It's up more than 50% this year and a staggering 435% since 2003, and as the Investment U research team knows, chronic supply shortages and unprecedented demand mean this boom is far from over. Investors willing to take immediate action on this unprecedented opportunity are in for the ride of their lives, and Investment U's Profit from Uranium is the perfect roadmap. As part of a new Investment U series created for the savvy investor, Investment U's Profit from Uranium provides you with the top picks and key strategies to take 3,150% returns or more from the most critical energy crisis in world history. While the facts are clear and the time is right, only investors who follow the advice found here will be prepared to capture the incredible profits that uranium has to offer.
Keywords: Investment analysis,Uranium industry